2016
DOI: 10.1609/aaai.v30i1.10169
|View full text |Cite
|
Sign up to set email alerts
|

Privacy-CNH: A Framework to Detect Photo Privacy with Convolutional Neural Network using Hierarchical Features

Abstract: Photo privacy is a very important problem in the digital age where photos are commonly shared on social networking sites and mobile devices. The main challenge in photo privacy detection is how to generate discriminant features to accurately detect privacy at risk photos. Existing photo privacy detection works, which rely on low-level vision features, are non-informative to the users regarding what privacy information is leaked from their photos. In this paper, we propose a new framework called Privacy-CNH t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…Templeman et al (2014) designed a method to automatically detect locations where the cameras should be turned off. (Tran et al 2016) was similar. Dai et al (2015) studied human activity recognition from extreme low resolution videos, different from conventional activity recognition literature that were focusing mostly on methods for images and videos with sufficient resolutions.…”
Section: Related Workmentioning
confidence: 62%
“…Templeman et al (2014) designed a method to automatically detect locations where the cameras should be turned off. (Tran et al 2016) was similar. Dai et al (2015) studied human activity recognition from extreme low resolution videos, different from conventional activity recognition literature that were focusing mostly on methods for images and videos with sufficient resolutions.…”
Section: Related Workmentioning
confidence: 62%
“…Image Privacy The PicAlert is somewhat biased as most of the private images in PicAlert is person-containing. To diversify private images, Yang et al (2020) extended PicAlert to include more types of images reported in the previous study (Tran et al 2016), such as driver licenses, ID cards, and legal documents. The Image Privacy dataset contains 13,910 private images and 24,615 public images.…”
Section: Datasetsmentioning
confidence: 99%
“…1. Following Tran et al (2016) and Yang et al (2020), we formulate privacy-leaking image detection as a binary classification task (i.e., predict whether…”
Section: Introductionmentioning
confidence: 99%
“…The proposed algorithm can be applied for personalized health-treatment in health-care data analytics, to shorten magnetic resonance imaging scanning sessions on conventional hardware, and to identify the privacy risks of images (Tran et al 2016) (He et al 2015) from object detection, etc. The thorough discussions and comparisons are left for future work.…”
Section: Applications In Business Unit (Bu)mentioning
confidence: 99%